Biochemical basis of CO2-related internal browning disorders in pears (Pyrus communisL. cv. Rocha) during long-term storage - Deuchande, Teresa (2017)
This study aimed at understanding the biochemical basis of internal browning disorders (IBDs) in 'Rocha' pear. For this purpose, the effects of storage under normal controlled atmosphere (CA) (3 kPa of O2 + 0.5 kPa of CO2) and IBD-inducing CA (1 kPa of O2 + 10 kPa of CO2) on the antioxidant and fermentative metabolisms and polyphenol oxidase (PPO) activity and phenolics concentration were studied. The higher IBD incidence in high CO2-stored fruits was positively correlated with fermentative metabolites and negatively with ascorbate and H2O2 concentrations, and it was linked to PPO activation. These results indicate that both the antioxidant and fermentative metabolisms are involved in the occurrence of IBD in 'Rocha' pear. From the integration of the biochemical and enzymatic data, a schematic model illustrating the effects of high CO2 and low O2 in 'Rocha' pears during long-term storage was constructed.